Optimal antithrombotic therapy after transcatheter aortic valve replacement: a comprehensive review - Thanh, Nguyen Van Thai; Hong, Myeong-Ki; Ko, Young-Guk (Frontiers in Cardiovascular Medicine, 2025)
Transcatheter aortic valve replacement (TAVR) has become a leading treatment for aortic stenosis, but managing thromboembolic and bleeding risks post-procedure remains challenging. This review examines current evidence on antithrombotic therapy after TAVR. Subclinical leaflet thrombosis is observed in 10%–20% of patients, though its clinical significance remains uncertain. Clinical valve thrombosis is rare. Current guidelines favor single antiplatelet therapy for patients without indications for long-term anticoagulation, as dual antiplatelet therapy increases bleeding risk without improving outcomes. For patients requiring long-term anticoagulation, monotherapy with direct oral anticoagulants or vitamin K antagonists is recommended to minimize bleeding. Ongoing trials aim to clarify optimal antithrombotic regimens and strategies for preventing subclinical leaflet thrombosis. Individualized therapy based on patient risk profiles is likely needed to improve the efficacy and safety of antithrombotic treatment post-TAVR.